THE INFLUENCE OF DIGITAL AND SOCIAL MEDIA MARKETING ON CONSUMER BEHAVIOUR - Komalpreet Kaur (Agora International Journal of Economical Sciences (AIJES), 2023)
In today's digitalized world, where internet and social media undoubtedly have a massive impact on our daily lives (including our buying decisions), it becomes indispensable for any manager or entrepreneur to be well aware about the influence of online marketing (also known as digital marketing) on consumer behaviour, so as to make the most profitable business decisions that are in their best interests. This study is an evaluation of some recently published articles and reports that tell about consumers in digital and social media settings. To write this article, a literature review is conducted and an attempt is made to highlight all the noteworthy ideas. In the end, the paper concludes traditional marketing is at the verge of disappearing as the marketers have found a better and more efficient way to reach the target audience.
Keywords: 330